2011
DOI: 10.2105/ajph.2011.300233
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum and Health Care: Evaluating and Managing Health Care's Vulnerability to Petroleum Supply Shifts

Abstract: Petroleum is used widely in health care-primarily as a transport fuel and feedstock for pharmaceuticals, plastics, and medical supplies-and few substitutes for it are available. This dependence theoretically makes health care vulnerable to petroleum supply shifts, but this vulnerability has not been empirically assessed. We quantify key aspects of petroleum use in health care and explore historical associations between petroleum supply shocks and health care prices. These analyses confirm that petroleum produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Climate constraints on regional water resources can in turn directly affect water supplies as well as indirectly impact the provision of electric power and food for urban residents (e.g., the recent power outage in India [Nessman ]); such supply chain risks can affect both economic activity and public health in cities (Hess et al. ). The multiple and multiscale risks posed to cities by infrastructure–environment interactions are illustrated in figure b.…”
Section: Infrastructures and Sustainable Citiesmentioning
confidence: 99%
“…Climate constraints on regional water resources can in turn directly affect water supplies as well as indirectly impact the provision of electric power and food for urban residents (e.g., the recent power outage in India [Nessman ]); such supply chain risks can affect both economic activity and public health in cities (Hess et al. ). The multiple and multiscale risks posed to cities by infrastructure–environment interactions are illustrated in figure b.…”
Section: Infrastructures and Sustainable Citiesmentioning
confidence: 99%
“…Indeed, localization identifies environmental sustainability as a key concern and promotes energy self-sufficiency alongside the broader administrative self-sufficiency conceived of by decentralization. Furthermore, localization of health systems is a much more recent concept, with no published applications related to health systems in LMICs and only recent work on developed-country health systems [ 11 , 57 ].…”
Section: Localizationmentioning
confidence: 99%
“…Hess et al have proposed “adaptive management” as a framework for the health system’s response to rising petroleum prices in the United States. Originating in the natural resources field, adaptive management is “useful for managing dynamic systems whose complexity complicates linear management decisions” [ 57 ]. Such management systems emphasize ongoing learning and continuous stakeholder input, with regular revision of management objectives, a range of management choices, and ongoing monitoring and evaluation [ 71 ].…”
Section: Localizationmentioning
confidence: 99%
“…Three decades ago, noting that health facilities are dependent on energy, Bailey 1 raised concerns about energy scarcity and energy costs in the context of the United States' (US) dependence on imported oil. More recently, several authors have warned that energy is a critical input for all health services, [2][3][4][5][6][7][8] and that there are several pathways through which energy scarcity and energy costs could affect health services. These include: the cost and availability of medical supplies and equipment; the cost and availability of healthrelated transport; the cost of lighting, heating and air conditioning health facilities; impacts on food security leading to increased demand on health services; and economic impacts that disrupt funding for health services.…”
mentioning
confidence: 99%
“…These concerns are shared by the general public, 9 and there is some empirical basis for them. In a time series analysis of US petroleum and health care prices between 1973 and 2008, Hess et al 5 found a 1% increase in oil price inflation was associated with a 0.03% increase in medical care prices after an eight‐month lag, although the effect was much stronger in the 1970s than in recent years.…”
mentioning
confidence: 99%